PENGARUH PEMBELAJARAN KEWIRAUSAHAAN, LITERASI DIGITAL, DAN PEMANFAATAN MEDIA SOSIAL TERHADAP MINAT BERWIRAUSAHA SISWA SMKN 1 SURABAYA - Tita Fitria; Putri Hestiningrum (Jurnal Pendidikan Tata Niaga (JPTN), 2026)
This study aims to determine the effect of entrepreneurship learning, digital literacy, and social media utilization on students' entrepreneurial interest at SMK Negeri 1 Surabaya. This study uses a quantitative approach with a causal associative method. The population in this study were 349 students of grade XI majoring in Digital Business, Accounting, and Management. Using a simple random sampling technique with a sample size of 187 students. The instrument used was an online questionnaire via Gform. Data processing used SPSS version 25. The results showed that the entrepreneurship learning variable influenced students' entrepreneurial interest. The digital literacy variable did not influence students' entrepreneurial interest. The use of social media influenced students' entrepreneurial interest. Simultaneously, entrepreneurship learning, digital literacy, and social media utilization influenced students' entrepreneurial interest.